2021
DOI: 10.1177/0954405421995669
|View full text |Cite
|
Sign up to set email alerts
|

Process capabilities of commercially pure titanium grade 2 formed through warm incremental sheet forming

Abstract: Commercially pure titanium (CP-Ti) Grade-2 has many applications due to its good weldability, strength, ductility, formability, and superior corrosion resistance. Although, CP-Ti Grade-2 can be formed at room temperature, however, it has lower ductility at room temperature. Therefore, heat treatment or thermal activation is required to increase its ductility and formability. In this paper, the process capabilities of CP-Ti Grade-2 to form the components through warm incremental sheet forming (ISF) has been inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…This implies that the conical objects are subjected to the plane strain condition during forming. The same observations are also reported in the literature [29,30].…”
Section: Forming Limit Diagramsupporting
confidence: 89%
“…This implies that the conical objects are subjected to the plane strain condition during forming. The same observations are also reported in the literature [29,30].…”
Section: Forming Limit Diagramsupporting
confidence: 89%
“…6 A few researchers have explored ISF for producing components with hard to form alloys but such works are rare. [7][8][9][10] However, ISF of Extra Deep Drawn (EDD) steel, one of the most important alloys used in the automobile industry is rarely discussed in the literature. EDD steel is used in applications where large strain deformation is required.…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al 18 performed the experiments of ISF and ET-ISF on the AA1050 sheet metal and revealed the minimum sheet thickness values after the deformation, which is close to the findings of this research work. Forming force (Fz) in the case of Titanium Grade 2 can be validated with the experimental work carried out by Kumar et al 29…”
Section: Resultsmentioning
confidence: 57%
“…In this research, global heating of the sheets was done during the finite element simulations of the ET-ISF process which can be done with the help of halogen lamps during experiments. 29 The schematic diagram of ET-ISF is shown in Figure 1(b). The mode of heat transfer during ET-ISF can be understood by Figure 1(c).…”
Section: Elevated Temperature Incremental Sheet Forming (Et-isf)mentioning
confidence: 99%